Development of genetic diversity, differentiation and structure over 500 years in four ponderosa pine populations - M. R. Lesser; T. L. Parchman; S. T. Jackson (Molecular Ecology, 2013)
Population history plays an important role in shaping contemporary levels of genetic variation and geographic structure. This is especially true in small, isolated range‐margin populations, where effects of inbreeding, genetic drift and gene flow may be more pronounced than in large continuous populations. Effects of landscape fragmentation and isolation distance may have implications for persistence of range‐margin populations if they are demographic sinks. We studied four small, disjunct populations of ponderosa pine over a 500‐year period. We coupled demographic data obtained through dendroecological methods with microsatellite data to discern how and when contemporary levels of allelic diversity, among and within‐population levels of differentiation, and geographic structure, arose. Alleles accumulated rapidly following initial colonization, demonstrating proportionally high levels of gene flow into the populations. At population sizes of approximately 100 individuals, allele accumulation saturated. Levels of genetic differentiation among populations ( F ST and Jost's D est ) and diversity within populations ( F IS ) remained stable through time. There was no evidence of geographic genetic structure at any time in the populations' history. Proportionally, high gene flow in the early stages of population growth resulted in rapid accumulation of alleles and quickly created relatively homogenous genetic patterns among populations. Our study demonstrates that contemporary levels of genetic diversity were formed quickly and early in population development. How contemporary genetic diversity accumulates over time is a key facet of understanding population growth and development. This is especially relevant given the extent and speed at which species ranges are predicted to shift in the coming century.